Tinjauan Waktu Tunggu Pelayanan Pasien BPJS di Rawat Jalan Rumah Sakit Islam Siti Khadijah Palembang - M. Ariq Dwi Rizky Paganini; Limisran Limisran; Nova Yulianto (Lembaga Pengembangan Kinerja Dosen, 2024)
Waiting time for healthcare services is a key indicator of quality, particularly for BPJS patients in outpatient settings. This study aims to examine the waiting time for BPJS patient services at Siti Khadijah Islamic Hospital Palembang and identify factors contributing to delays. A quantitative descriptive method was employed, with data collected through observation, questionnaires, and checklists. The sample consisted of 97 BPJS outpatient respondents. Findings revealed that 68% of patients experienced waiting times exceeding 60 minutes, surpassing the established standard. Key factors contributing to delays included inconsistent doctor schedules and high patient volumes in specific clinics, such as geriatrics. The study concludes that waiting times need improvement through the implementation of written Standard Operating Procedures (SOPs), increased medical staff, and optimized service schedules. The findings emphasize the importance of effective time management in enhancing service quality and patient satisfaction.